2021
DOI: 10.1111/liv.14905
|View full text |Cite
|
Sign up to set email alerts
|

Over time evaluation of glycaemic control in direct‐acting antiviral‐treated hepatitis C virus/diabetic individuals with chronic hepatitis or with cirrhosis

Abstract: Background: Data concerning the impact of hepatitis C virus (HCV) cure on type 2 diabetes mellitus (T2DM) are controversial. The aim of the study was to evaluate the effects of anti-HCV direct-acting antiviral (DAA) treatments on long-term glucose control in HCV/T2DM patients with chronic hepatitis C (CHC) or with cirrhosis. Methods: One hundred and eighty-two consecutive HCV/T2DM patients who achieved a viral clearance by DAA treatment were enrolled. Seventy or 182 of them had CHC, and 112 had cirrhosis. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…A recent Italian study by Cacciola et al confirmed a significant reduction in HbA1c in HCV patients after treatment with DAAs that was persistent over time only in noncirrhotic subjects. 33 Nevertheless, Huang et al, in contrast with previous studies, found no changes in BMI and HbA1c, but the study was limited by a small sample size. 22 With regard to lipid profile, much evidence is consistent with a clear relationship between the HCV biologic cycle and lipoproteins metabolism.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A recent Italian study by Cacciola et al confirmed a significant reduction in HbA1c in HCV patients after treatment with DAAs that was persistent over time only in noncirrhotic subjects. 33 Nevertheless, Huang et al, in contrast with previous studies, found no changes in BMI and HbA1c, but the study was limited by a small sample size. 22 With regard to lipid profile, much evidence is consistent with a clear relationship between the HCV biologic cycle and lipoproteins metabolism.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, no data relative to CV events were reported, not permitting speculations about a future increase in CV risk. A recent Italian study by Cacciola et al confirmed a significant reduction in HbA1c in HCV patients after treatment with DAAs that was persistent over time only in noncirrhotic subjects 33 . Nevertheless, Huang et al, in contrast with previous studies, found no changes in BMI and HbA1c, but the study was limited by a small sample size 22 .…”
Section: Discussionmentioning
confidence: 94%
“…Contrary to what was observed with interferon-based therapies, MetS does not seem to affect the sustained virologic response to treatment with direct-acting antivirals (DAA) [ 12 ]. HCV cure following DAA treatment generally leads to improvements in glucose homeostasis [ 12 , 13 , 14 ] but has no long-term impact on glucose metabolism in patients suffering from liver cirrhosis [ 14 , 15 ]. Pre-DAA diabetes increases mortality and liver-related events independently of HCV cure [ 12 ], and diabetes is also an independent risk factor of de novo hepatocellular carcinoma after DAA treatment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic hepatitis C virus (HCV) infection are at greater risk of metabolic disorders such as hyperlipidemia, hepatic steatosis, insulin resistance, metabolic syndrome, and diabetes mellitus (Chaudhari et al 2021 ). Direct acting antivirals (DAA) can now cure HCV, leading to liver fibrosis regression, less liver necroinflammation, a lower risk of hepatic decompensation, amelioration of glycemic control, and lower liver-related and overall mortality (Kang et al 2021 ; Roche et al 2018 ; Huang et al 2021 ; Cacciola et al 2021 ). However, for patients with diabetes and/or cirrhosis, the benefits in terms of glycemic control and the lower risks of hepatocellular carcinoma (HCC) and mortality are not as strong (Cacciola et al 2021 ; Váncsa et al 2021 ; Benhammou et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Direct acting antivirals (DAA) can now cure HCV, leading to liver fibrosis regression, less liver necroinflammation, a lower risk of hepatic decompensation, amelioration of glycemic control, and lower liver-related and overall mortality (Kang et al 2021 ; Roche et al 2018 ; Huang et al 2021 ; Cacciola et al 2021 ). However, for patients with diabetes and/or cirrhosis, the benefits in terms of glycemic control and the lower risks of hepatocellular carcinoma (HCC) and mortality are not as strong (Cacciola et al 2021 ; Váncsa et al 2021 ; Benhammou et al 2021 ). Moreover, obesity and hepatic steatosis are risk factors for HCC development after HCV cure (Minami et al 2021 ; Ji et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%